Inequality and Trust - Henrik Jordahl (Research Institute of Industrial Economics (IFN), 2007)
This paper reviews the literature on economic inequality and trust. Cross-country studies, within-country studies, and experiments all suggest that economic inequality exerts a negative influence on trust. Four mechanisms are proposed to explain the negative relationship: social ties (or networks), inference on social relationships (to see inequality as a signal of untrustworthy behavior), conflicts over resources, and opportunity cost of time. Social ties receive the strongest empirical support, but there is also some evidence in favor of inference on social relationships. Conflicts over resources and opportunity cost of time are contradicted by important pieces of evidence.
Keywords: C23; D31; Z13; 330; Trust; Inequality; Social Capital; Social Ties; Networks; Vertrauen; Einkommensverteilung; Soziales Netzwerk; Social Capital; Welt